eHealth in Chronic Diseases - Torres-Sanchez, Irene; Valenza, Marie Carmen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book provides a review of the management of chronic diseases (evaluation and treatment) through eHealth. Studies that examine how eHealth can help to prevent, evaluate, or treat chronic diseases and their outcomes are included.